2021
DOI: 10.1177/21582440211005453
|View full text |Cite
|
Sign up to set email alerts
|

How Does Family Intimacy Predict Self-Esteem in Adolescents? Moderation of Social Media Use Based on Gender Difference

Abstract: The current study explored the multiple effects of social media use and its moderation mechanism between intimate family environment and self-esteem in adolescents. In all, 1,040 males and 1,201 females below age 25 have participated in this study. Hypothesis and research questions were proposed and examined by statistical analysis, consisting of statistical description, Pearson’s correlation analysis, independent-samples t test, multiple linear regression, simple-slope analysis, and moderation plot. Supportiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Although studies of parental trust and the subsequent effects on adolescents’ later behaviors are very important, cultural representation is also essential before drawing a general conclusion. 39 This study is not enough to speak for the vast cultural environment of the African region. Further studies can be done by involving other age groups (ie, primary school age group), examining the interrelation of the variables and creating a clear picture of parenting in African culture and its associated outcome on children’s behavior in their later age.…”
Section: Limitations and Suggestions For Further Studiesmentioning
confidence: 92%
See 2 more Smart Citations
“…Although studies of parental trust and the subsequent effects on adolescents’ later behaviors are very important, cultural representation is also essential before drawing a general conclusion. 39 This study is not enough to speak for the vast cultural environment of the African region. Further studies can be done by involving other age groups (ie, primary school age group), examining the interrelation of the variables and creating a clear picture of parenting in African culture and its associated outcome on children’s behavior in their later age.…”
Section: Limitations and Suggestions For Further Studiesmentioning
confidence: 92%
“… 36 Other studies showed self-regulated learning (mediator) as the mechanisms through which such causal relationship works. 37 , 38 The relationship of similar variables may also be positively affected by students’ age and gender, 39 while youths’ reports (on their parental trust) predicted their academic achievement more than their parents’ reports. 16 Although most of the existing literature on parental trust and support has extracted data from adolescents (students) by means of self-reporting, less is known about the influence of self-esteem in such causal relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid expansion of internet usage and the increasing prevalence of social media platforms have raised concerns about their impact on individuals’ moral values in the digital era [ 1 , 2 ]. Internet addiction (IA), also known as problematic internet use, has garnered significant attention from researchers and experts across various disciplines [ 2 , 3 ]. It refers to excessive or compulsive internet use that leads to significant impairment in different aspects of individuals’ lives over an extended period [ 3 ].…”
Section: Introductionmentioning
confidence: 99%